Prospective cohort studies of beta-trace protein and mortality in haemodialysis patients and patients undergoing coronary angiography - Enko, Dietmar; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; März, Winfried (Pharmacopsychiatry, 2018)
AbstractBackground. Beta-trace protein (BTP) is a low-molecular-weight glycoprotein, which may serve as an endogenous biomarker of kidney function and cardiova
Gesehen am 18.02.2020